Lessons learned from mucolipidosis II 'knock-in' mice... - Coutinho, Maria Francisca (2014)
Original paper: Kollmann K, Damme M, Markmann S, Morelle W, Schweizer M, Hermans-Borgmeyer I, Röchert AK, Pohl S, Lübke T, Michalski JC, Käkelä R, Walkley SU, Braulke T. Lysosomal dysfunction causes neurodegeneration in mucolipidosis II 'knock-in' mice. Brain. 2012;135:2661-75.